Flow of a Williamson fluid over a stretching sheet - Nadeem,S. (2013)
In the present article, we have examined the two dimensional flow of Williamson fluid model over a stretching sheet. The governing equations of pseudoplastic Williamson fluid are modelled and then simplified by using similarity transformations and boundary layer approach. The reduced equations are then solved analytically with the help of homotopy analysis method. The physical features of the model are presented and discussed through graphs.